Pharmacologic stabilization of hypoxia-inducible transcription factors protects developing mouse brain from hypoxia-induced apoptotic cell death - Trollmann, Regina; Richter, Markus; Jung, Susan; Walkinshaw, G.; Brackmann, Florian (Neuroscience, 2014)
Accumulation of hypoxia-inducible transcription factors (HIFs) by prolyl-4-hydroxylase inhibitors (PHI) has been suggested to induce neuroprotection in the ischemic rodent brain. We aimed to investigate in vivo effects of a novel PHI on HIF-regulated neurotrophic and pro-apoptotic factors in the developing normoxic and hypoxic mouse brain.Neonatal mice (P7) were treated with PHI FG-4497 (30-100mg/kg, i.p.) followed by exposure to systemic hypoxia (8% O2, 6h) 4h later. Cerebral expression of HIF?-subunits, specific neurotrophic and vasoactive target genes (vascular endothelial growth factor (VEGF), adrenomedullin (ADM), erythropoietin (EPO), inducible nitric oxide synthase (iNOS)) as well as pro-apoptotic (BCL2/adenovirus E1B 19-kDa protein-interacting protein 3 gene (BNIP3), immediate early response 3 (IER3)) and migratory factors (chemokine receptor 4 (CXCR4), stromal cell-derived factor 1 (SDF-1)) was determined (quantitative real-time (RT)., Western blot analysis) in comparison to controls. Apoptotic cell death was analyzed by terminal desoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) and cleaved caspase 3 (CC3) staining.Under normoxic conditions, FG-4497 treatment significantly induced the accumulation of both HIF-1? and HIF-2? isoforms in developing mouse brain. In addition, there was a significant up-regulation of HIF target genes (VEGF, ADM, EPO, CXCR4, p<0.01) with FG-4497 treatment compared to controls supporting functional activation of the HIF proteins. Under hypoxia, differential target gene activation was observed in the developing brain including additive effects of FG-4497 and hypoxia on mRNA expression of VEGF and ADM as well as a dose-dependent down-regulation of iNOS. BNIP3 but not IER3 mRNA levels significantly increased in hypoxic brains pre-treated with high-dose FG-4497 compared to controls. Of special interest, FG-4497 treatment significantly diminished apoptotic cell death, quantified by TUNEL and CC3-positive cells, in hypoxic developing brains compared to controls.PHI treatment modulates neurotrophic factors known to be crucially involved in hypoxia-induced cerebral adaptive mechanisms as well as early brain maturation. Pre-treatment with FG-4497 seems to protect the developing brain from hypoxia-induced apoptosis. Present observations provide basic information for further evaluation of neuroprotective properties of PHI treatment in hypoxic injury of the developing brain. However, potential effects on maturational processes need special attention in experimental research targeting HIF-dependent neuroprotective interventions during the very early stage of brain development.
EVALuna2:18900